Essays for Richard Ellmann : omnium gatherum - Ellmann, Richard, 1918-1987; Dick, Susan (McGill-Queen's University Press, 1989)
Ellmann's sensitivity to what it meant to be an artist shaped his work from the outset: "The life of an artist ... differs from the lives of other persons in that its events are becoming artistic sources even as they command his present attention. Instead of allowing each day, pushed back by the next, to lapse into imprecise memory, he shapes again the experiences which have shaped him." Richard Ellmann died in 1987. His life and work have touched the lives of many. Some of the essays in this collection commemorate Richard Ellmann and his commitment to Twentieth Century literature: most provide a continuing investigation of the Twentieth Century literature to which he devoted his carrer. Contributors include: Alison Armstrong, Daniel Albright, Christopher Butler, Carol Cantrell, Jonathan Culler, Elizabeth Butler Cullingford, Andonis Decavelles, Rupin Desai, Susan Dick, Terence Diggory, Terry Eagleton, Rosita Fanto, Charles Feidelson, James Flannery, Charles Huttar, Bruce Johnson, John Kelleher, Brendan Kennelly, Frank Kermode, Declan Kiberd, Peter Kuch, Bruce Johnson, James Laughlin, A. Walton Litz, Dominic Manganiello, Ellsworth Mason, Christie McDonald, Dougald McMillan, Sean O'Mordha, Vivian Mercier, Mary T. Reynolds, William K. Robertson, Joseph Ronsley, S.P. Rosenbaum, Ann Saddlemyer, Sylvan Schendler, Daniel Schneider, Fritz Senn, Jon Stallworthy, Lonnie Weatherby, Thomas Whitaker, and Elaine Yarosky.